Pillz: smart pill dispenser system for senior care - Shari, Anis Najihah; Rahmat, Mohammad Hafidz; Abdul Aziz, Azlinda (College of Computing, Informatics, and Mathematics, 2025)
The Smart Pill Dispenser System functions as a modern system which enables elderly users and patients to handle their medicine schedules effectively. The system combines Raspberry Pi with infrared sensor, servo motor and mobile application using Firebase as a real-time monitoring platform. The dispenser runs its automated pill distribution process through timed rotations of the specific pill slot to guarantee proper dosage. The mobile application receives information from an infrared sensor when it detects pill consumption. The system activates an alert by sending notifications for the user when the pill remains unretrieved. The mobile app enables remote monitoring which enables caregivers and family members to check medication adherence patterns. Firebase provides users with automatic data synchronization capabilities that allow device-to device data accessibility. Real-time alerts and IoT integration with automation in the Smart Pill Dispenser system promote medication adherence which decreases the chance of patients missing their doses or taking them twice. The proposed solution seeks to develop a dependable system that simplifies medication administration specifically for elderly patients and people dealing with persistent health conditions.